All Days 2016
DOI: 10.2118/180274-ms
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Rock/Fluid Interactions of Sodium and Calcium Brines with Ultra-Tight Rock Surfaces and their Impact on Improving Oil Recovery by Spontaneous Imbibition

Abstract: This work is a novel attempt to analyze rock/brine and oil/brine interactions in heterogeneous unconventional liquid reservoir rocks and the effect of these interactions on oil recovery. There is very limited literature on the impact of brine salinity on shale wettability alteration and spontaneous imbibition experiments. This study includes a comprehensive approach that analyzes rock-fluid interactions through contact angle and zeta potential measurements followed by imbibition studies monitored by CT scan te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Oil recovery using LSW in conventional formations can exceed that obtained using produced high-salinity brines . Laboratory-scale oil recoveries from ULR cores indicate that several mechanisms may be responsible for the oil recovery observed during the immersion of oil-rich shale cores in water or LSW. Possible mechanisms of oil recovery by LSW include wettability alteration, , detachment of clays, multicomponent ion exchange, desorption of polar components from rock surfaces, formation of cracks in shale due to LSW imbibition, and osmosis …”
Section: Chemical Eor Using Water In Ulrsmentioning
confidence: 99%
“…Oil recovery using LSW in conventional formations can exceed that obtained using produced high-salinity brines . Laboratory-scale oil recoveries from ULR cores indicate that several mechanisms may be responsible for the oil recovery observed during the immersion of oil-rich shale cores in water or LSW. Possible mechanisms of oil recovery by LSW include wettability alteration, , detachment of clays, multicomponent ion exchange, desorption of polar components from rock surfaces, formation of cracks in shale due to LSW imbibition, and osmosis …”
Section: Chemical Eor Using Water In Ulrsmentioning
confidence: 99%
“…M.K. Valluri et al revealed that the interactions between the ultra-tight cores and Na + , Ca 2+ ions enhanced the recovery efficiency of tight reservoirs [36]. Q. Lan et al explored the relationship between water loss via imbibition and soaking time of tight sandstone reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…The pH gradient theory discussed above also makes a similar prediction. Several other studies have also demonstrated that the ζ-potential at mineral surfaces decreases as the brine salinity reduces [56,58,203,249,256], with NaCl brine giving lesser ζ-potential reduction than divalent cations brines [56,256] and ζ-potential becomes constant within experimental error at concentrations beyond 0.4 M (23,400 ppm) [58,203].…”
Section: Electrical Interactionsmentioning
confidence: 83%